(untitled) (Bangladesh Journal of Pharmacology, 2015)
Methanol and aqueous root extracts of Indigofera serpentinicola were investigated for their phytochemical, antimicrobial and cytotoxic properties. Phytochemical analysis showed the presence of alkaloids, saponins, tanins, terpenoids, cardiac glycosides, phenols, reducing sugars oils and fats in both extracts. Flavanoids were only detected in the methanolic extract. Antimicrobial activity was evaluated using the Kirby-Bauer disk diffusion method. The extracts showed low activity against Staphylococus aureus, Cornybacterium diptheriae, Pseudomonas aeruginosa and Salmonella enterica and no activity against Escherichia coli. The diameters zones of inhibition ranged between 3-10 mm. The aqueous extract had higher activity showing zones of inhibition of 10 mm against S. enterica. Brine shrimp lethality test showed LC50 values which ranged from 0.079-0.158 mg/mL, showing that the extracts were highly toxic.